COMPLEX CLAUSE OF BAHASA INDONESIA FROM THE POINT OF VIEW OF SYSTEMIC FUNCTIONAL LINGUISTIC - Frans I Made Brata (University of Muhammadiyah Purwokerto, 2012)
This paper discusses the meaning of the complex clause by a series of processes that are combined in a logical of the two clauses. Complex clause can be combined through one of two logical-semantic relationships that is expansion or projection. Systemic Functional Linguistics approach is used to describe the five texts taken at random. The five texts are: (1) Gembala dan malaikat, (2) Pendahuluan, (3) Melakukan Studi Gender dalam Bahasa, (4) Korporasi, Kerja dan Kultur, dan (5) Gara-gara Dilarang Bertemu (1) Shepherd and angels, (2) Introduction, (3) Doing Gender in Language Studies, (4) Corporations, Employment and Culture, and (5) Due to Divorce, No Meet Pets. The analysis of the five texts is not opposed but complementary to one another. By using a qualitative descriptive method, it was found two types of logical-semantic relations: (1) Expansion, and (2) projection. Integrating through one of the logical-semantic relations: expansion or projection is realized through a system of mutual dependence or taxis that can be divided into paratactic and hypotactic. Key words: Clause complex, expansion, projection